2010
DOI: 10.1176/foc.8.2.foc165
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Well-Being in Person-Centered Mental Health Care

Abstract: An understanding of the mechanisms of personality development provides a systematic way to promote health as an integrated state of physical, mental, social, and spiritual well-being. Individual differences in personality are causal antecedents of the full range of psychopathology. The maturation with integration of personality appears to be an important mechanism by which diverse modalities of treatment promote wellness and reduce illness. First, the authors review the relationship between personality and a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 121 publications
(138 reference statements)
5
88
0
9
Order By: Relevance
“…One study has even indicated that this increase in ' self-directedness ' has also predictive value for changes in depressive symptoms as measured with BDI (Mazza et al 2009). Therefore, character dimensions may modulate the expression of mood states (Farmer et al 2003 ;Cloninger, 2004 ;Cloninger et al 2010) and our results may shed light on why both depressive symptoms and ' selfdirectedness ' improve during serotonin-altering psychopharmacological treatment.…”
Section: Discussionmentioning
confidence: 70%
“…One study has even indicated that this increase in ' self-directedness ' has also predictive value for changes in depressive symptoms as measured with BDI (Mazza et al 2009). Therefore, character dimensions may modulate the expression of mood states (Farmer et al 2003 ;Cloninger, 2004 ;Cloninger et al 2010) and our results may shed light on why both depressive symptoms and ' selfdirectedness ' improve during serotonin-altering psychopharmacological treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Self-transcendence decreases through age 45 and then later increases again in response to the challenges of ultimate situations like suffering and imminent mortality (Cloninger, 2003;Josefsson et al, 2013a). The maturation of character traits appears to be a way to promote and maintain health by facilitating healthy self-regulation of emotional reactions and lifestyle choices (Cloninger et al, 2010;. In particular, higher levels of the character traits of Selfdirectedness, Cooperativeness, and Self-transcendence are all associated with positive emotions, satisfying social relations, and perceived physical health .…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…In prior work we have shown that individual differences in personality influence the physical, mental, and social aspects of health and well-being (Cloninger et al, 2010;. Personality affects the individual's emotional state, autonomic stability, immune response, capacity to selfregulate stress, as well as health behavior and response to medical treatments.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…The importance of all three traits of character is further evidenced by the findings of "third-wave psychotherapies" that have sought to address the limitations of earlier "behavioural" and "cognitive-behavioural" approaches 5,11,42 . Cognitive-behavioural therapies are effective in promoting self-directedness and to some extent cooperativeness, but do not address self-transcendence.…”
Section: The Crucial Importance Of Ternary Awareness For Progress In mentioning
confidence: 99%
“…Cognitive-behavioural therapies are effective in promoting self-directedness and to some extent cooperativeness, but do not address self-transcendence. In contrast, third-wave psychotherapies, such as Mindfulness-based Cognitive-behavioural therapy, Dialectical Behaviour Therapy, and Acceptance and Commitment Therapy, reduce drop-outs and improve physical, mental, and social health outcomes by adding mindfulness and related spiritual practices that also promote selftranscendence 5,11,42 .…”
Section: The Crucial Importance Of Ternary Awareness For Progress In mentioning
confidence: 99%